Dorado, O., D. M. Arias, R. Ramírez y M. Sousa. 2005. Leguminosas de la Sierra de Huautla. Imágenes y descripciones. CEAMISH-UAEM / CONABIO. Cuernavaca, Morelos, México. 176 pp - Valenzuela Galván, David (Instituto de Ecología, A.C., 2008)
Reseña de libro.